UPAYA MENINGKATKAN KOMITMEN ORGANISASI MELALUI PERAN KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI: SEBUAH KAJIAN PUSTAKA - syaiful bakhri; Dede Harjadisastra; M. Zain Khiswari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
High commitment from employees is what the company really wants. The more highly committed employees, the overall company productivity will increase, and the company can survive in its business competition. Commitment to the organization is an important behavioral dimension that can be used to evaluate the strength of workers to stay in an organization. Therefore, the management of an organization or company needs to continue to encourage the creation of commitment from members of the organization. Several factors that can increase organizational commitment are carried out through the role of transformational leadership and organizational culture. The purpose of this research is to analyze the role of transformational leadership and organizational culture on organizational commitment. This research is a qualitative research by searching the literature on the variables discussed. Considering that this research is a qualitative research, further research is recommended to use quantitative methods where researchers seek data directly in the field and use statistical tests, especially on variables that still have different results